Protection of Trade Secrets in the Field of Information Technology - Georgeta Modiga; Andreea Miclea; Gabriel Avramescu (EIRP Proceedings, 2018)
“Trade secret” can be a formula, compilation, program, method, technique, or process that derives independent economic value, actual or potential, from not being generally known to the public. While the economic value of a trade secret is usually difficult to determine, it can provide an important competitive advantage for the owner. In this article, we emphasize the importance of trade secrets for firms and the economy and the risks to trade secrets posed by computerization and by departing employees. Next, we present an outline of the legal framework for the protection of trade secrets and summarize a number of trade secret cases. Finally, we draw our conclusion.